Lectures on LHC physics - Plehn, Tilman (Lecture Notes in Physics, 2012)
When trying to apply the solid knowledge of quantum field theory to actual LHC physics - in particular to the Higgs sector and certain regimes of QCD -  one inevitably meets an intricate maze of phenomenological know-how, common lores and other, often historically grown intuition about what works and what not. These lectures are intended to be a brief but sufficiently detailed primer on LHC physics that will enable graduate students and any newcomer to the field to find their way through the more advanced literature as well as helping them to start work in this very timely and exciting field of research.